2015
DOI: 10.7857/jsge.2015.20.3.065
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Investigation of Fluoride Migration in the Soil Affected by an Accidental Hydrofluoric Acid Leakage

Abstract: The hydrofluoric acid (HF) leakage accident occurred on September 2012 in Gumi, Korea affected the surrounding soils and plants. In this study, we investigated fluoride migration in Gumi area through geochemical properties of soil-liquid phase (pore water F and water-soluble F). The concentrations of porewater F and water-soluble F were obtained from N.D (Not detected) to 9.79 mg/L and from 0.001 to 21.4 mg/L, respectively. F in pore water seemed to be affected by artificial and natural origin, and PHREEQC res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Aldaco et al [44] observed that while adding doses of calcium ions to fluoride present in wastewater, the ions (Ca 2+ and F -) form an insoluble product (CaF 2 ). Additionally, CaF 2 formation confirmed the possibility of CaF 2 precipitate formation in the reaction between calcium ions and soluble F present in soil using PHREEQC, a geochemical model [45].…”
Section: Non-carcinogenic Risk (Hq) = Add/rfdo + Ade/rfc + Addw/rfdosupporting
confidence: 58%
“…Aldaco et al [44] observed that while adding doses of calcium ions to fluoride present in wastewater, the ions (Ca 2+ and F -) form an insoluble product (CaF 2 ). Additionally, CaF 2 formation confirmed the possibility of CaF 2 precipitate formation in the reaction between calcium ions and soluble F present in soil using PHREEQC, a geochemical model [45].…”
Section: Non-carcinogenic Risk (Hq) = Add/rfdo + Ade/rfc + Addw/rfdosupporting
confidence: 58%
“…To avoid the di culties of a pretreatment process in incineration/distillation or alkaline fusion, the combination of aqua regia extraction and the determination of the uorine concentration in water with UV/vis spectrophotometry according to the U.S. standard method was proposed (Kwon et al, 2015). A soil sample sieved through a 200 mesh sieve was mixed with 10 mL aqua regia, and the mixture was heated at 70 ℃ for 2 h, ltered with the glass ber-type B lter, and diluted to 100 mL with deionized water.…”
Section: Aqua Regia Extraction-uv/vis Spectrophotometrymentioning
confidence: 99%
“…In general, uorine is assumed to prevent tooth decay; thus, a project on the control of uorine in tap water was implemented in South Korea (Kwon et al, 2015). However, excessive exposure can cause uorine accumulations in teeth and bones (i.e., uorosis; Czerwinski et al, 1988); in general, less than 1 mg/L uorine is injected into drinking water to prevent tooth decay.…”
Section: Introductionmentioning
confidence: 99%
“…Although small amounts of uorine in water help keep teeth healthy (Kwon et al, 2015), high concentrations of uorine in plants and animals can cause toxic effects (Pushnik and Miller, 1990;Patra et al, 2000;Yu et al, 2022). Furthermore, the accumulation of uorine in human bodies may harm human health by promoting diseases such as osteoporosis (Grandjean, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Various chemical decomposition methods, including the incineration/distillation-UV/vis spectrophotometry method (Willard and Winter, 1933), alkaline fusion-selective ion electrode method (McQuaker and Gurney, 1977), and aqua regia extraction-UV/vis spectrophotometry (Kwon et al, 2015), have been used to determine the total concentrations of uorine in a solid matrix. In South Korea, the total uorine concentration in the soil is commonly determined using the incineration/distillation-UV/vis spectrophotometry method (a standard method to analyze the uorine concentration in soil), and remediation action is decided accordingly.…”
Section: Introductionmentioning
confidence: 99%